Level of self-care and self-efficacy among hypertension patient in medical wards at Hospital Universiti Sains Malaysia - Husin, Raja Fatin Aida Raja (Universiti Sains Malaysia, 2016)
Self-care among hypertension patient was crucial in managing aspects of their health by adopting skills and behavior that prevent disease, limit illness and restore health in future. Self-care and self-efficacy in hypertension were important part in management of hypertension. This study was to determine level of self-care and self-efficacy among hypertension patient in medical ward at Hospital USM. A cross-sectional study on selfcare activities among hypertension patients was carried out at medical ward in Hospital USM. This study involved subjects from medical wards which were 7 Utara and 7 Selatan. A total of 105 subjects completed the questionnaires by convenience sampling technique that the fits inclusion criteria. Data was statistically analyzed using the software package SPSS version 22. Among 105 respondents (n=105), 87.6% respondents reported being adherent to hypertension medication, 43.8% low salt dietary, 46.7% engaged in physical activity, 88.6% smoking cessation, 57.1% followed good weight management. Respondents were high in good self-efficacy to manage hypertension which was 60%. Meanwhile for poor self-efficacy were 40%. By the logistic regression, sociodemographic was associated with self-care. Age, gender were significant associated with medication adherence (p-value<0.05). Age was significant associated with low salt diet (p-value<0.05). Gender was significant associated with nonsmoking and weight management (p-value<0.05). For self-efficacy, there were only nonsmoking was associated while the other are not statistically associated to self-care. In conclusion, this research finding indicated there was patient had better adherence to self-care in hypertension in medical ward at Hospital USM. Self-care such as medication adherence, nonsmoking and weight management were common in their daily life in managing hypertension. Better self-care can prevent complication of hypertension which can cause reduce quality of life and mortality.